(untitled) (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2025)
This study examines the relationship between parenting styles and the development of responsibility in children from single-parent and nuclear families. Using a mixed-methods approach with 150 children aged 12-16 and their parents, results indicate significant differences in responsibility development pathways between family structures, with authoritative parenting showing strongest correlations with responsibility across both family types. The study reveals that while children in nuclear families initially showed higher responsibility scores, these differences became non-significant when controlling for authoritative parenting practices. Qualitative findings further illuminate how single parents can effectively implement authoritative strategies through consistent routines, clear expectations, and supportive communication. The research underscores that parenting quality transcends family structure in fostering responsibility development.